The Potential of Sequential Fermentations in Converting C1 Substrates to Higher-Value Products - Stark, Christina; Münßinger, Sini; Rosenau, Frank; Eikmanns, Bernhard J.; Schwentner, Andreas (Frontiers in Microbiology, 2022)
Today production of (bulk) chemicals and fuels almost exclusively relies on petroleum-based sources, which are connected to greenhouse gas release, fueling climate change. This increases the urgence to develop alternative bio-based technologies and processes. Gaseous and liquid C1 compounds are available at low cost and often occur as waste streams. Acetogenic bacteria can directly use C1 compounds like CO, CO2, formate or methanol anaerobically, converting them into acetate and ethanol for higher-value biotechnological products. However, these microorganisms possess strict energetic limitations, which in turn pose limitations to their potential for biotechnological applications. Moreover, efficient genetic tools for strain improvement are often missing. However, focusing on the metabolic abilities acetogens provide, they can prodigiously ease these technological disadvantages. Producing acetate and ethanol from C1 compounds can fuel via bio-based intermediates conversion into more energy-demanding, higher-value products, by deploying aerobic organisms that are able to grow with acetate/ethanol as carbon and energy source. Promising new approaches have become available combining these two fermentation steps in sequential approaches, either as separate fermentations or as integrated two-stage fermentation processes. This review aims at introducing, comparing, and evaluating the published approaches of sequential C1 fermentations, delivering a list of promising organisms for the individual fermentation steps and giving an overview of the existing broad spectrum of products based on acetate and ethanol. Understanding of these pioneering approaches allows collecting ideas for new products and may open avenues towards making full use of the technological potential of these concepts for establishment of a sustainable biotechnology.